2020
DOI: 10.1016/j.omtn.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Functional Mechanisms of Somatic Copy-Number Alterations Based on Dysregulated ceRNA Networks across Cancers

Abstract: Somatic copy-number alterations (SCNAs) drive tumor growth and evolution. However, the functional roles of SCNAs across the genome are still poorly understood. We provide an integrative strategy to characterize the functional roles of driver SCNAs in cancers based on dysregulated competing endogenous RNA (ceRNA) networks. We identified 44 driver SCNAs in lower-grade glioma (LGG). The dysregulated patterns losing all correlation relationships dominated dysregulated ceRNA networks. Homozygous deletion of six gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…miRNAs are common negative regulators of gene expression. According to the competitive endogenous RNA (ceRNA) mechanism, endogenous lncRNAs with miRNA target sites have the potential to act as natural miRNA sponges, which suppress the expression of miRNA targets by competitively binding and inhibiting miRNAs ( 40 ). Notably, some lncRNAs (PVT1 and FENDRR) have been identified to regulate miR-15a-5p expression via the ceRNA network ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are common negative regulators of gene expression. According to the competitive endogenous RNA (ceRNA) mechanism, endogenous lncRNAs with miRNA target sites have the potential to act as natural miRNA sponges, which suppress the expression of miRNA targets by competitively binding and inhibiting miRNAs ( 40 ). Notably, some lncRNAs (PVT1 and FENDRR) have been identified to regulate miR-15a-5p expression via the ceRNA network ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The driver genes identified by our method significantly overlapped with these known cancer gene sets (hypergeometric test, P < 0.05, Table 1 ). We then further compared our method with the other three previous methods, which also identified driver copy number alterations [ Ping et al, 2020 ; Zhou et al, 2017 , and DriverDBv3 ( Liu et al, 2020 )]. The results showed that our method could also significantly capture the driver genes identified by other methods with the Ping et al (2020) , Zhou et al (2017) (hypergeometric test, P = 1.84e-05 for Ping et al (2020) , P = 4.23e-12 for Zhou et al (2017) , Table 1 ), but not significantly with DriverDBv3(hypergeometric test, P = 0.175, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We then further compared our method with the other three previous methods, which also identified driver copy number alterations [ Ping et al, 2020 ; Zhou et al, 2017 , and DriverDBv3 ( Liu et al, 2020 )]. The results showed that our method could also significantly capture the driver genes identified by other methods with the Ping et al (2020) , Zhou et al (2017) (hypergeometric test, P = 1.84e-05 for Ping et al (2020) , P = 4.23e-12 for Zhou et al (2017) , Table 1 ), but not significantly with DriverDBv3(hypergeometric test, P = 0.175, Table 1 ). Among them, Ping et al (2020) could directly dissect long non-coding RNAs (lncRNAs) functional roles in cancers based on dysregulated ceRNA network induced by SCNAs but was limited in identifying potential driver SCNAs with low expression levels and SCNA frequencies, however, Zhou et al (2017) and DriverDBv3 cannot dissect driver roles of genes in cancers in a direct manner ( Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“… 43 , 44 , 45 , 46 Clarifying the molecular mechanisms and processes of the pathogenesis of HCC and identifying promising biomarkers are essential for identifying new therapeutic targets and improving patients’ outcome with this disease. 47 , 48 , 49 According to reports, the ceRNA regulatory network participates in the occurrence and development of many human cancers, including lung cancer, 50 gastric cancer, 51 and pancreatic cancer. 52 However, to our knowledge, few studies have focused on a comprehensive ceRNA regulatory network to predict the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%